THE USE OF SONGS AS A PROMPT IN GENRE-BASED APPROACH IN TEACHING NARRATIVE TEXT : A Case Study in a Senior High School in Bandung - Ilyasa, Sintia Hamidah (2013)
The research paper entitled, "The use of Songs as a Prompt in Genre-based Approach in Teaching Narrative Text: a Case Study in a Senior High School in Bandung", aimed to examine in what stages of the genre-based approach (GBA) that songs as a prompt can be incorporated in teaching narrative text. Moreover, the study investigated to what extent songs as a prompt can help the students in writing narrative text. This study was conducted in one senior high school in Bandung using a case study research design. The data were collected from the observations, document analysis, and interview. The findings of this study show that, songs can be incorporated in every stage in GBA including Building Knowledge of Field, Modeling of Text, Joint Construction, and Independent Construction. Furthermore, the analysis reveals that songs as a prompt can help the students to write narrative text in several aspects, as in helping the students to understand context and social purpose of narrative text, generating ideas to write narrative texts, enhancing students' vocabularies and the use of expressions in writing narrative text, and promoting students' motivation. Regarding this, it is recommended to use songs a as a prompt incorporated in GBA to teach writing in any text types, such as descriptive, recount, etc.